1998
DOI: 10.1093/oxfordjournals.pcp.a029442
|View full text |Cite
|
Sign up to set email alerts
|

A MADS Box Gene Homologous to A G is Expressed in Seedlings as well as in Flowers of Ginseng

Abstract: To study the flower development of ginseng, a MADS box cDNA (GAG2) was isolated and characterized. A comparison of the deduced amino acid sequence of GAG2 with the sequences of other MADS box proteins showed higher amino acid identities with AG (71%) from Arabidopsis thaliana, which is specifically expressed in stamens and carpels of flowers than with AGL genes (30 to 60%), suggesting that GAG2 is a ginseng homologue of AG. However northern blot analysis showed that GAG2 was expressed in seedlings. As the gins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Similar phenotypes were also observed in 35S::AP3/35S::PI and 35S::SEP3 transgenic plants (Pelaz et al 2001, Honma andGoto 2001). In addition to causing sepal and petal conversion into carpel-and stamen-like structures, ectopic expression of AG or its orthologues from heterologous plants also produced an early-flowering phenotype (Mizukami and Ma 1992, Mizukami and Ma 1997, Bradley et al 1993, Kempin et al 1993, Schmidt et al 1993, Pnueli et al 1994b, Kang et al 1995, Kater et al 1998, Kim et al 1998, Rutledge et al 1998, Tandre et al 1998, Yu et al 1999, Winter et al 1999. This indicated that some ABCDE MADS box genes and their orthologues are able to regulate floral initiation once ectopically expressed in plants.…”
Section: Introductionsupporting
confidence: 58%
“…Similar phenotypes were also observed in 35S::AP3/35S::PI and 35S::SEP3 transgenic plants (Pelaz et al 2001, Honma andGoto 2001). In addition to causing sepal and petal conversion into carpel-and stamen-like structures, ectopic expression of AG or its orthologues from heterologous plants also produced an early-flowering phenotype (Mizukami and Ma 1992, Mizukami and Ma 1997, Bradley et al 1993, Kempin et al 1993, Schmidt et al 1993, Pnueli et al 1994b, Kang et al 1995, Kater et al 1998, Kim et al 1998, Rutledge et al 1998, Tandre et al 1998, Yu et al 1999, Winter et al 1999. This indicated that some ABCDE MADS box genes and their orthologues are able to regulate floral initiation once ectopically expressed in plants.…”
Section: Introductionsupporting
confidence: 58%
“…This is supported by the fact that mutation in AG, the most representative C functional gene, caused the homeotic conversion of stamen to petal and carpel to sepal (Bowman et al 1989). In addition, ectopically expressing AG or its homologues from heterologous plants caused the conversion of sepals and petals to carpel-and stamen-like structures which were similar to those observed in ap2 mutants (Mizukami and Ma 1992, Mizukami and Ma 1997, Kempin et al 1993, Schmidt et al 1993, Bradley et al 1993, Pnueli et al 1994, Kang et al 1995, Kim et al 1998, Kater et al 1998, Tandre et al 1998, Rutledge et al 1998, Yu et al 1999, Winter et al 1999.…”
Section: Introductionsupporting
confidence: 55%
“…During third growth year, the indeterminate inflorescence attached by a single peduncle developed from the primordium forms from second-year growth plants. Unlike studies in annual plants which have multiple axillary meristems originated from the shoot apical meristem during inflorescence and flower development (Zhang and Yuan 2014), ginseng plant usually produces a single inflorescence from the primordium contained within the underground bud of a rhizome formed during June to August of the previous year (Baranov 1966;Thompson 1987;Kim et al 1998). The feature of ginseng in producing the inflorescence primordium in the previous year and requiring winter dormancy for further development of inflorescence is a characteristic of perennial plants (Meloche and Diggle 2003;Albani and Coupland 2010).…”
Section: Characteristic Morphology Of Ginseng Inflorescence and Flowersmentioning
confidence: 99%